Attitudes and Support Strategies of Parents to Promote English-Indonesian Bilingualism in Children - Ika Apriani Fata; Chairina Nasir; Najwa Alifah (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2022)
The goal of this study was to look into parents' attitudes toward encouraging English-Indonesian bilingualism in their children, as well as their support strategies for doing so. This study used a mixed-method approach to collect both quantitative and qualitative data. The quantitative data was collected using a questionnaire, while the qualitative data was collected during the interviews using open-ended questions. Twenty mothers who raise bilingual (English-Indonesian) children took part in the study. The researcher collected data using a questionnaire and an interview. The majority of parents prefer English-Indonesian bilingualism for their children, according to the findings of this study. By being actively involved in their children's language development, parents always make efforts to maintain their children's bilingual skills. The support systems that parents provide for their children, as well as the degree of support provided in English language learning, appear to differ. To make the learning process effective and successful, parents focus on their children's interests while developing Indonesian-English skills for them.